Transport and diffusion in boundary layers of turbulent channel flow - Sanwald, Sven; Warnatz, Jürgen; Wolfrum, Jürgen (Reactive flows, diffusion and transport, 2007)
To investigate the transport and the diffusion of scalars in a turbulent channel flow, direct numerical simulations (DNS) are performed and experiments with the same geometry have been set up to examine details of the near-wall region. Transport and diffusion are observed with flow-tagging methods. In one setup the deformation of a line of tracer-molecules, placed perpendicular to the flow direction, is investigated. Furthermore the seeding and detecting of tracer-molecules into the boundary layer has been realized in two different configurations, in order to investigate species transport between the bulk flow and the boundary layer.